Assessment of pre-donation glomerular filtration rate: going back to basics. Issue 3 (14th September 2021) - Mariat, Christophe; Mjøen, Geir; Watschinger, Bruno; Sever, Mehmet Sukru; Crespo, Marta; Peruzzi, Licia; Oniscu, Gabriel C; Abramowicz, Daniel; Hilbrands, Luuk; Maggiore, Umberto
Abstract: The 2017 version of the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines is the most recent international framework for the evaluation and care of living kidneys donors. Along with the call for an integrative approach evaluating the long-term end-stage kidney disease risk for the future potential donor, several recommendations are formulated regarding the pre-donation glomerular filtration rate (GFR) adequacy with no or little consideration for the donor candidate's age or for the importance of using reference methods of GFR measurements. Herein, we question the position of the KDIGO guidelines and discuss the rationale and modalities for a more basic, but no less demanding GFR evaluation enabling a more efficient selection of potential kidney donors.